Characterisation of plastic-based sanitary personal protective equipment following supercritical CO₂ sterilisation: A reuse strategy - Helga K. Ruiz; José M. Gómez-Salazar; Lourdes Calvo; Albertina Cabañas (Journal of CO2 Utilization)
The global demand for single-use personal protective equipment (PPE) is rapidly increasing. Most PPE items are composed of plastics, which often end up in landfills or oceans, causing significant environmental harm. Additionally, the disposal of PPE is costly, as it is classified as biological waste. In this study, sanitary PPE components were sterilized using supercritical CO2 at 40°C and 10 MPa, with the addition of small amounts of additives (<0.1 %). Specifically, sterilisation was achieved using as additives mixtures of water, H2O2 and acetic anhydride, or peracetic acid. The materials were characterized before and after treatment using FTIR, DSC, and SEM-EDX to assess whether the sterilization process affected the physical and chemical properties of the PPE components. Results showed that masks, gowns, coveralls, caps, and shoe covers were largely unaffected by the treatment, while nitrile gloves and protective glasses exhibited alterations. No traces of the additives were detected in the treated materials, as they were carried away by the CO2 during depressurization. These findings demonstrate that supercritical CO2 sterilization is a viable method for reusing certain PPE components or recycling them as polymeric raw materials, offering an environmentally friendly alternative to incineration. The significant potential of this technology for hospital applications is evident.